Analysis of Displacement Response of the Ermenek Dam Monitored by an Integrated Geodetic and Pendulum System - Alcay, S.; Yigit, Cemal Ozer; Inal, C.; Ceylan, A. (Iran University of Science and Technology, 2018)
© 2017, Iran University of Science and Technology. This paper studies the structural behavior of the Ermenek arch dam, the second highest dam in Turkey. The investigated period covers the stage of the last-quarter part of first filling (1 and 1/2 year) and the begging of its operational lifetime (1 year). Displacement responses of the dam to temperature load and water load are assessed in detail based on both geodetic and pendulum monitoring records. In addition, the present study explores the possibility and advantage of integrating pendulum-measured signals with geodetic-measured signals for the dam deformation monitoring. The analysis results reveal that pendulum-derived displacements at four gallery levels, along the vertical cross section of the dam, which exhibit periodicity and linear trend with different slope due to seasonal temperature oscillation and linearly increased reservoir level, respectively. Comparative evaluation of the results shows that there is very good agreement between geodetic-derived displacement in radial direction at the middle of the crest and corresponding pendulum-derived displacement.